Emojis in German and Croatian Facebook comments during the 2018 World Cup - Perić, Marija; Pavić Pintarić, Anita (Slavia Centralis, 2021)
In internet communication, grapho-stylistic tools are used to replace the elements of non-verbal communication. In this paper, emojis are explored as facial expressions (cf. Wahyuni and Budi 2018: 194) and they also have functions that relate to a particular communicative attitude, i.e. to emotionally enhance the statement and help reconstruct the communication context. It is precisely the possibilities of emotionally reinforcing the statement that are the focus of this article. The corpus consists of emojis in Facebook comments on the 2018 World Cup in German newspaper Bild and Croatian newspaper 24 sata. The aim of this article is to compare emojis and their use in Croatian and German based on the theory of evaluation.
Keywords: emojis; non-verbal communication; Facebook football comments; German; Croatian